Levels of Rat Cellular RNA Homologous to Either Kirsten Sarcoma Virus or Rat Type-C Virus in Cell Lines Derived from Osborne-Mendel Rats - Scolnick, Edward M. (1974)
DNA transcripts from V-NRK and RT21c rat type-C viruses were found to differ in their sequence homology to Kirsten and Harvey sarcoma viruses. V-NRK DNA transcripts consistently had homology to Kirsten and Harvey sarcoma virus, whereas RT21c DNA transcripts did not. To explain the differences, the nucleic acids and structural proteins of the two type-C viruses, released from each of two cell lines derived from Osborne-Mendel rats, were analyzed by molecular hybridization and competition radioimmunoassays. The p30 and p12 structural proteins of the two viruses were found to be highly related immunologically. In the V-NRK virus preparation, two sets of distinct RNA sequences were found in approximately equal amounts. One set is homologous to Ki-SV, and the other homologous to RT21c. In contrast, the RT21c virus preparation was found to contain a different ratio of these sequences. In this case the RT21c-like RNA sequences are present in 100-fold excess as compared to the additional Ki-SV specific sequences. Both NRK and RT21c cells contain in their DNA the full complement of Ki-SV homologous sequences, but NRK cells express much higher levels of these Ki-SV sequences in their RNA. These additional sequences, not homologous to RT21c, which are detected in uninfected NRK cellular RNA or V-NRK rat virus, could also be detected in the 60-70S RNA from a Moloney mouse type-C virus released from the NRK cells infected with the Moloney type-C virus. The results suggest that type-C viruses released from NRK cells incorporate species of RNA present in NRK cells which are homologous to Kirsten and Harvey sarcoma viruses. Either these sequences are of cellular origin, or rat cells contain two endogenous viruses with completely distinct nucleic acid sequences.